Analisis Kredit Bermasalah Sebagai Antisipasi Terhadap Krisis Perbankan di Indonesia (Kasus pada Kredit Properti BTN) - Erni Ambarwati; Wildan Syafitri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
Bank as an intermediary financial institutions will be able to be the cause of the crisis resulting from increased non performing loans in the form of arrears interest payments, principal loan or both. This research focuses to assess the potential due to credit crisis in the country troubled by knowing variable influence monetary is inflation, interest rate on mortgage loans, exchange rate and bank performance is LDR, CAR and BOPO against non performing loans of the Bank Tabungan Negara in the short term and long term. Loans at a bank can be seen from the comparison loans and the amount of the credits distributed known as the ratio of the Non Performing Loan ( NPL). The analysis of the data used in this study is Erorr Correction Model (ECM)/ model correction of a fault. Using this method be analyzed the short-term and long-term between the independent variable of the dependent variable and engineering analysis to correct imbalances long-term (speed of adjusment). The results of this study shows that in the short term positive effect of inflation variables, interest rates on mortgage loans have positive effect, exchange rate not have negative effects, LDR have positive effect, CAR not have positive effect and BOPO have positive effect on the non-performing loans at Bank Tabungan Negara. While in the long run variable inflation it has some positive effects, interest rates on mortgage loans have a negative effect, exchange rate not have negative effects, LDR have positive effects, CAR have positive effects and BOPO have positive effects on the non performing loans at Bank Tabungan Negara. Increase in numbers non performing loans at Bank Tabungan Negara during a period of research make bank potentially facing the crisis if trust banking customers, investors and markets decline so withdrawing their customers in large numbers or bank rush that can disturb liquidity at Bank Tabungan Negara. Key Words: Non Performing Loans, Inflation, Interest Rate on Mortage Loan, Exchange Rate, LDR, CAR, BOPO, Banking Crisis, ECM Model